Attitudes of patients and clinicians in relation to the at‐risk state for psychosis. Issue 4 (17th June 2013) - Welsh, Patrick; Tiffin, Paul A.
Abstract: Aim: In the last decade, advances have been made in identifying young people who may be at relatively high risk (HR) of developing psychosis. Given the controversial and experimental nature of the HR concept, the attitudes and experiences of mental health professionals and patients are likely to influence practice in this area. Previous work has been published that has speculated on the potential risks and advantages of identifying and intervening within the HR state. However, few have attempted to capture the attitudes and experiences of patients and professionals towards this concept. This article provides, via the collation of existing research reports, a reflection on the views, attitudes and experiences of these key stakeholders. Methods: A narrative review of the literature was undertaken focussing upon the following key areas: mental health professionals' attitudes towards the HR concept, patients' attitudes towards the HR concept, attitudes of patients towards potential treatments and attitudes of professionals towards HR treatments. Results: Relatively few published studies focusing on the attitudes and experiences of patients and mental health professionals exist. However, there is some evidence that both professionals and affected individuals view the HR concept as worthy of diagnosis and intervention. Expressed treatment preferences appear to vary, dependent on the group of individuals surveyed. Conclusions: Further systematic studies of patient and professional preferences, in relation to identification and intervention, are desirable in order to explore the way that the HR denotation is personally interpreted and the extent to which it affects patient and practitioner behaviour.